Проблемы среднего образования, влияющие на формирование фундaментальной базы знаний выпускников школ и пути их решения - Деменкова, Светлана Дмитриевна (НТУ "ХПИ", 2011)
Авторы статьи анализируют проблемы высшей школы, которые обусловлены отставанием комплексных реформ в среднем образовании. В статье рассмотрены перечень причин, влияющих на низкий уровень фундаментальных знаний по естественным наукам выпускников средних школ, а также предложены пути их решения

The authors of the article analyse the problems of higher school, which are conditioned lag of complex reforms in secondary education. The list of reasons which influence on the low level of fundamental knowledges on natural sciences of graduating students of middle schools is considered in the article, and also the ways of their decision are offered
Problems of secondary education of, which influence on forming of fundomental'noy of base knowledges of graduating students of schools and ways of their decision
Keywords: проблемы высшей школы; комплексные реформы; студенты технических вузов; естественные науки; учитель; ученик